Determinants of national savings in Malaysia / Noorra Ibrahim and Nur Shazreena Zakaria - Ibrahim, Noorra; Zakaria, Nur Shazreena (Faculty of Business and Management, 2016)
Saving is an important indicator of economic development, where it indicates the finances for further action towards the development and other economic growth. The purpose of this study is to identify the determinants of national savings in Malaysia. The problem statement regarding this research is on the slow economic growth and also downturn of the investment sector. There are several variables that have been selected as the potential variables that could be the determinants of national savings; namely inflation rate, government expenditure, money supply (M2), age dependency ratio and per capita income. The method used in this study is using time series data, and run in E-views program which includes normality test, regressions and diagnostic tests. This study indicates significant relationship to national savings in single linear regression for variables namely; inflation rate, money supply and per capita income. While for multiple regressions, the results indicate that inflation rate, government expenditure, age dependency ratio and per capita income have significant impact to national savings.